KESIAPAN BELAJAR MANDIRI MAHASISWA UT DAN SISWA SMA UNTUK BELAJAR DENGAN SISTEM PENDIDIKAN TINGGI TERBUKA DAN JARAK JAUH DI INDONESIA - Islam, Samsul (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2010)
The research aims to find out Self Directed Learning Readiness (SDLR) of potential students and prospective students (high school students) to learn by open and distance learning (ODL) in Indonesia. Research conducted by survey method. The population were high school students who are considered grade 12 as a potential candidate ODL student, a freshman, and ODL student at the Open University (UT). SDLR levels were measured by questionnaires Self-Directed Learning Readiness Scale (SDLRS) developed by Guglielmino (1989). The resultsshowedthat the SDLR level ofhigh schoolstudentswere statisticallylower than theSDLR level of UTstudents, bothnew studentsandprevious students. However, there wereno statisticallysignificant differencesbetween theSDLR level ofnew studentsandpreviousstudents ofUT. ScoreSDLRSobtainedshowthat theUTstudenthasaveragelevels ofSDLR. This means thatUTstudentscansuccessfullylearnindependentlybutthey are not very responsibletodeterminelearning needs, plan, implement, andevaluatetheir own learning. UTstudentswhohave theSDLRlevelaboveaverage are over 55years students.